PENTINGNYA MEMAHAMI DAN MENJAGA MARTABAT MANUSIA DI ERA MODERN: ANALISIS PADA DEKLARASI DIGNITAS INFINITA - Andro Golung; Fiorenza Waworundeng (Pineleng Theological Review, 2026)
Amid rapid technological advancement, globalization, and socio-political transformation, the concept of human dignity faces renewed ethical and anthropological challenges. This article critically examines Dignitas Infinita, the 2024 Declaration of the Dicastery for the Doctrine of the Faith, focusing on its theological articulation of human dignity within a Christian anthropological framework. Employing qualitative textual and theological analysis, the study argues that the declaration advances a non-reductionist understanding of dignity as ontological, inherent, and inalienable, grounded in creation imago Dei  and fulfilled through redemption in Christ. The article analyses how  Dignitas Infinita  responds to contemporary threats to human dignity, including digital instrumentalization, utilitarian ethics, social injustice, environmental degradation, and systemic violence such as war, poverty, human trafficking, and discrimination. It contends that the declaration offers a coherent normative framework that resists the objectification of the human person and reaffirms dignity as a foundational principle for ethics and human rights discourse. The study concludes that  Dignitas Infinita contributes significantly to contemporary moral theology by calling for shared moral responsibility in the pursuit of justice, solidarity, and sustainable human flourishing.